Study of intellectual developmental work of teacher candidates with primary school students - Daribayeva, Zh.A.; Kargapoltseva, N.A. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2023)
The article examines the study of the work of teacher candidates on intellectual development with primary school students. The scientific works of scholars from far and near abroad have studied the work of teacher candidates aimed at developing the intellectual abilities of schoolchildren. The analysis of methodologies, and scientific experience of scholars on the development of intellectual abilities of schoolchildren is carried out. We were guided by the conclusions of Russian scientists about the professional development of teacher candidates. To determine the level of readiness of teacher candidates for intellectual and developmental work with primary school students, interviews and questionnaires were conducted with students of a local educational institution. Primary school teachers have identified the qualifications necessary for a teacher to work with students intellectually. Analyzing the results of the survey and interviews, the ways of solving the current problem were considered. Based on the results of the research work, it was concluded that in the conditions of improving the didactic and pedagogical training of teacher candidates, work is being carried out to form the readiness of teacher candidates to work on the intellectual development of primary school students.
Болашақ бастауыш сынып мұғалімдерінің оқушылармен интеллектуалды дамыту жұмыстарының зерттелуі
Изучение интеллектуальной развивающей работы будущих учителей начальных классов с учащимися
Keywords: intelligence; intellectual developmental work; intellectual skills; teacher candidates; primary school student; pedagogical skills; pedagogical qualification